Pengaruh Metode Ekspresi Bebas terhadap Hasil Keterampilan Cetak Tinggi Menggunakan Bahan Tumbuhan pada Siswa Kelas XI SMA - Salsabilah Balqis; Sugito Sugito (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
This study aims to determine whether the free expression method will have a significant impact on the relief printing skills of class XI students of SMA Swasta Tunas Bangsa Kwala Begumit. This study compares the demonstration method with the free expression method for high printing practice materials. Data were collected using a high printing practice test using plant materials. The data that had been collected were then analyzed using statistical analysis in the form of data normality tests using the Liliefors method, followed by homogeneity tests using the Bartlett method, then for comparison tests using the t-test. The results of the study proved that there was a significant increase in students' high printing skills. This was evidenced by the experimental class t-test value obtained that = 10.90 with a price of 1.6753 with dk 52 and a real level of 0.05, then 10.90 1.6753 was obtained and there was an increase of 20% with a comparison of the average post-test value between the experimental class (85.93) > control class (74.96). This shows a significant increase in students' skills in high printing practice using plant materials